Providing organic food to urban consumers: case studies of supermarkets in Bangkok and metropolitan area. Issue 5 (May 2020) - Kantamaturapoj, Kanang; Marshall, Alan
Abstract: This study aimed to 1) explore the information flow by which supermarkets attempt to communicate with consumers, and 2) make a preliminary evaluation of the strategies used by supermarkets to promote organic food to consumers specifically within the Bangkok Metropolitan Area. Nine supermarket outlets located at the headquarters of nine supermarket chains were observed. Eleven informants from four supermarket chains were interviewed. The results found that supermarkets in Thailand provided rich information about organic food via standard certification, a Participatory Guarantee System, storylines and illustrations involving farmers. The retailers attempted to offer organic food in a way that is convenient to urban consumers' lifestyles. However, the retailers did not attempt to offer special discounts or marketing promotions since they believed that the consumers knowledgeable of organic food would be willing to pay premium price. Two valuable recommendations can be drawn from this research. Firstly, the retailers should provide more information about the formal control systems and authenticity of organic food in order to foster trust and to allow consumers to assess its benefits. Secondly, the retailers should continue offering 'ready to eat' organic food since it can be of significance in relation to the lifestyle of urban Thai consumers. Abstract : Sustainable food; Retailer; Supermarket, Organic food; Retailers' strategy; Food provision; Bangkok; Urban consumer, Qualitative research in food marketing; Business policy; Sustainable business; Corporate entrepreneurship; Corporate social responsibility; Marketing; Sustainable development, Business.